Rethinking humanitarian intervention in the 21st century - Warren, Aiden; Grenfell, Damian (Edinburgh University Press, 2017)
Since the Cold War, humanitarian interventions have transitioned through a range of stages. These 12 essays focus on the challenges associated with interventions, conflict and attendant human rights violations, unmitigated and systematic violence, state re-building, and issues associated with human mobility and dislocation. Each chapter is linked to the rest through three defining themes that permeate the book: the 'global and the local' in the context of interventions; extending and broadening the definitions associated with interventions; and mapping the evolution of interventions over the last three decades.